Let a , b , c be complex numbers satisfying
a + b + c = a b c = 1
and
3 a b + b c + a c = a 2 1 + b 2 1 + c 2 1
The sum of absolute values of all possible a b + b c + a c can be written as m n , where n and m are positive coprime integers. What is n + m ?
This problem is posed by Zi Song Y.
Details and assumptions
You may read up on Absolute Value .
n is allowed to be 1.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Suppose a b = x , b c = y , c a = z .Then we have a b c ( a + b + c ) = a b ⋅ b c + b c ⋅ c a + c a ⋅ a b = x y + y z + z x = 1 .From the second equation,we obtain :$$\frac{x+y+z}{3}=\frac{(ab)^2+(bc)^2+(ca)^2}{(abc)^2}$$ $$=x^2+y^2+z^2$$ $$=(x+y+z)^2-2(xy+yz+zx)$$ $$=(x+y+z)^2-2$$Thus,by substituting x + y + z = a ,we have the quadratic equation:$$3a^2-a-6=0$$ $$|a 1|+|a 2|=\frac{\sqrt{73}+1}{6}+\frac{\sqrt{73}-1}{6}=\frac{\sqrt{73}}{3}$$ So, n + m = 7 3 + 3 = 7 6
From the second equality, we can see that
3 a b + b c + c a = a 2 1 + b 2 1 + c 2 1
= a 2 b 2 + b 2 c 2 + c 2 a 2 because a b c = ( a b c ) 2 = 1
= ( a b + b c + c a ) 2 − 2 a b c ( a + b + c )
= ( a b + b c + c a ) 2 − 2 because a b c = a + b + c = 1
let a b + b c + c a = x so 3 x = x 2 − 2
so we have a quadratic equation 3 x 2 − x − 6 = 0
whose solution are 6 1 ± 1 + 4 × 6 × 3
= 6 1 ± 7 3
the absolute value of the solution are
6 7 3 + 1 and 6 7 3 − 1
and the sum is 3 7 3 = m n
so m + n = 7 3 + 3 = 7 6
For convenience, let x = a b + a c + b c .
We need to solve for x :
3 x = a 2 1 + b 2 1 + c 2 1
We will transform the RHS to get a function of only x .
a 2 1 + b 2 1 + c 2 1 = a 2 b 2 c 2 1 ( b 2 c 2 + a 2 c 2 + a 2 b 2 ) = ( ∗ )
Since a b c = 1 , this equals
( ∗ ) = b 2 c 2 + a 2 c 2 + a 2 b 2 = ( ∗ )
Now we use the identity p 2 + q 2 + r 2 = ( p + q + r ) 2 − 2 p q − 2 p r − 2 q r with p = b c , q = a c , r = a b
( ∗ ) = ( b c + a c + a b ) 2 − 2 a b c 2 − 2 a b 2 c − 2 a 2 b c = ( ∗ )
Because a b c = 1 , and also a + b + c = 1 , this simplifies to
( ∗ ) = ( b c + a c + a b ) 2 − 2 ( c + b + a ) = x 2 − 2 .
Now we have the following equation to solve:
3 x = x 2 − 2 , which has the roots x 1 = 6 1 + 7 3 and x 2 = 6 1 − 7 3
∣ x 1 ∣ + ∣ x 2 ∣ = 3 7 3
Therefore, the solution is 7 6 .
say ab+bc+ca = x and a^2b^2 + b^2c^2 + c^2a^2 = y
(ab+bc+ca)^2 = a^2b^2+b^2c^2+c^2a^2+2(ab^2c+abc^2+a^2bc) = a^2b^2+b^2c^2+c^2a^2+2abc(a+b+c) = a^2b^2+b^2c^2+c^2a^2+2 so x^2 = y+2
and
\frac{ab+bc+ca}{3} = \frac{1}{a^2} + \frac{1}{b^2} + \frac{1}{c^2} = \frac{a^2b^2+b^2c^2+c^2a^2}{a^2b^2c^2} = \frac{y}{1} = y So x = 3y y = \frac{x}{3} so x^2 = \frac{x}{3} + 2 3x^2-x-2 = 0 x = \frac{1 \pm \sqrt{73}}{6} only two possible solution so |x 1| + |x 2| = \frac{\sqrt{73}}{3} so m = 73 n = 3 m+n = 76
Problem Loading...
Note Loading...
Set Loading...
3 a b + b c + c a = a 2 1 + b 2 1 + c 2 1
3 a b + b c + c a = ( a 1 + b 1 + c 1 ) 2 − 2 ( a b c a b + b c + c a )
3 a b + b c + c a = ( a b c a b + b c + c a ) 2 − 2
3 a b + b c + c a = ( a b + b c + c a ) 2 − 2
Let (ab + bc + ca) = x
3 x = x 2 − 2
3 x 2 − x − 6 = 0
x= 6 1 ± 7 3
Therefore, ∣ x 1 ∣ + ∣ x 2 ∣ = 6 7 3
n=73 and m=3
Therefore, m+n=76